2013
DOI: 10.5899/2013/cna-00139
|View full text |Cite
|
Sign up to set email alerts
|

Analytic approximate solution for the Bratu's problem by optimal homotopy analysis method

Abstract: In This paper, we present analytic approximate solutions for Bratu's problem with high accuracy for different values of λ. We solve this nonlinear problem without any approximations or transformation in the problem and we successfully obtain the two branches of solutions for different values λ using homotopy analysis method. A new efficient approach is proposed to obtain the optimal value of convergence controller parameter ℏ to guarantee the convergence of the obtained series solution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 19 publications
0
8
0
1
Order By: Relevance
“…(3.12) is linear and thus can be easily solved, especially by means of symbolic computation software such as Mathematica, Maple, Matlab. Yabushita et al [29] and Mohamed S. Mohamed et al [30,31,32] applied the homotopy analysis method to nonlinear ODE's and suggested the so called optimization method to find out the optimal convergence control parameters by minimum of the square residual error integrated in the whole region having physical meaning. Their approach is based on the square residual error.…”
Section: The Optimal Homotopy Analysis Methods (Oham)mentioning
confidence: 99%
See 1 more Smart Citation
“…(3.12) is linear and thus can be easily solved, especially by means of symbolic computation software such as Mathematica, Maple, Matlab. Yabushita et al [29] and Mohamed S. Mohamed et al [30,31,32] applied the homotopy analysis method to nonlinear ODE's and suggested the so called optimization method to find out the optimal convergence control parameters by minimum of the square residual error integrated in the whole region having physical meaning. Their approach is based on the square residual error.…”
Section: The Optimal Homotopy Analysis Methods (Oham)mentioning
confidence: 99%
“…The approximate solutions of Eq. (5.24) take the following form at β = 1, 32) and so on. According to the HAM, we can conclude that…”
Section: Applicationsmentioning
confidence: 99%
“…3 when a ¼ 2. The integer order case was solved using the semi-analytic and numerical techniques (Hassan and El-Tawil, 2011;Hassan and Semary, 2013;Jalilian, 2010;Kafri and Khuri, 2016;Semary and Hassan, 2015) using spline method (Jalilian, 2010), variational iteration method (Semary and Hassan, 2015), homotopy analysis method (Hassan and El-Tawil, 2011;Hassan and Semary, 2013) and other methods.…”
Section: Numerical Examplesmentioning
confidence: 99%
“…al [28] and Mohamed S. Mohamed et. al [29][30][31] applied the homotopy analysis method to nonlinear ODE's and suggested the so called optimization method to find out the optimal convergence control parameters by minimum of the square residual error integrated in the whole region having physical meaning. Their approach is based on the square residual error.…”
Section: Preliminaries and Notationsmentioning
confidence: 99%